2006
DOI: 10.1590/s0101-81752006000400009
|View full text |Cite
|
Sign up to set email alerts
|

Development of Myrmeleon brasiliensis (Navás) (Neuroptera, Myrmeleontidae), in laboratory, with different natural diets

Abstract: Antlions larvae are sit-and-wait predators that capture arthropod prey in conical sand pits. The aim of this paper were to determine the effect of different natural diets [leaf-cutting ants (Atta spp.), fruit fly larvae (Anastrepha spp. and Ceratitis capitata) and mixed diet (Atta spp. plus fruit fly larvae)] on the development of larvae and pupae of M. brasiliensis (Navás, 1914) and to estimate the number and size of prey caught in each instar and on each kind of diet. The average duration (days) of the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 16 publications
(15 reference statements)
1
18
0
8
Order By: Relevance
“…At the same time, smaller energy savings may have afforded a more rapid metamorphosis, as the emerging adults in this situation (of constant disturbance) were smaller. Missirian et al, (2006) observed that although the size of adult M. brasiliensis may be affected by diet quality, the pupal development time did not change.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…At the same time, smaller energy savings may have afforded a more rapid metamorphosis, as the emerging adults in this situation (of constant disturbance) were smaller. Missirian et al, (2006) observed that although the size of adult M. brasiliensis may be affected by diet quality, the pupal development time did not change.…”
Section: Discussionmentioning
confidence: 85%
“…Data from Eltz (1997) suggest that the process of change in Myrmeleon mobilis Hagen, 1888 can be accelerated in individuals that are well nourished and suffer less disruption to their traps. Missirian et al, (2006) observed that M. brasiliensis fed with a high energy diet also had an accelerated development. In contrast, it is possible that organisms that live in unstable environments show lower growth rates, even when prey are provided.…”
Section: Discussionmentioning
confidence: 95%
“…(Hymenoptera: Formicidae) (Aluja et al, 2005); the myrmeleontid Myrmeleon brasileiensis (Navás) (Neuroptera) (Missirian et al, 2006); some species rove beetles, probably Belonuchus Nordmann (Coleoptera: Staphylinidae), and Carabidae (Coleoptera) (Uchôa, M. A., unpubl.). Galli & Rampazo (1996) listed the carabids Calosoma granulatum Perty, Calleida sp., and Scarites sp., and the staphylinids: Belonuchus haemorrhoidalis (Fabricius), and Belonuchus rufipennis (Fabricius), among the predators of Anastrepha spp.…”
Section: Insect Predators On Anastrepha Species and Ceratitis Capitatamentioning
confidence: 99%
“…More than 1,500 species in 201 genera and 14 tribes of myrmeleontids are described (Stange 2004).The larvae of Myrmeleon species are generalist predators of arthropods that move along the soil surface. They are known for their foraging behavior: building funnel-shaped traps in friable or sandy soil, under which they wait for prey that falls inside these snares (Napolitano 1998;Missirian et al 2006).…”
mentioning
confidence: 99%
“…The pupal stage is completed inside the cocoon. Adult emergence of M. brasiliensis occurs approximately one month after pupation (Arnett & Gotelli 2001;Missirian et al 2006). All species of insects are vulnerable to the attack of natural enemies, which in many cases are important regulators of population density of the host or prey (Hawkins et al 1997).…”
mentioning
confidence: 99%